MHD free-convection and mass transfer flow through a porous medium with heat source - Jha B.K.; Prasad R. (My University, 2025)
An analytical study is performed to examine the heat source characteristics on the free-convection and mass transfer flow past an impulsively started infinite non-conducting vertical plate of a viscous, incompressible electrically-conducting fluid under the action of a uniform magnetic field through porous medium. The effects of various parameters on the velocity field are extensively discussed. © 1991 Kluwer Academic Publishers.